Estresse oxidativo na leishmaniose visceral canina - Almeida, Breno Fernando Martins de [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Oxidative stress occurs due to an imbalance between oxidants and antioxidant defenses. Considering that dogs with leishmaniasis may develop uremia, which affects the oxidative metabolism and apoptosis of neutrophils, we proposed to investigate the hypothesis that oxidative stress, alteration of oxidative metabolism and apoptosis of neutrophils in dogs varies according to stage of leishmaniasis and that uremia, commonly occurs in late stages of disease, would contribute to such variations. To this, we evaluated plasma markers of oxidative stress (total antioxidant capacity, lipid peroxidation, glutathione, uric acid, bilirubin and albumin), superoxide production (method of nitroblue tetrazolium reduction and flow cytometry with the probe hydroethidine), and viability and apoptosis rate (morphological method and flow cytometry using annexin V-PE system) on neutrophils from dogs with leishmaniasis classified according to the LeishVet Consensus in moderate stage of the disease, very severe stage when uremia is installed and dogs with uremia negative for leishmaniasis, comparing them to healthy dogs. Leishmaniasis regardless of stage and uremia cause oxidative stress with reduced total antioxidant capacity, which may be related to greater induced production of superoxide and stimulated apoptosis observed in these groups. While spontaneously, neutrophils of dogs in very severe stage and with uremia had lower viability, increased apoptosis and higher lipid peroxidation, suggesting that uremia is the cause of such changes. Can be concluded that the intensity of oxidative stress does not vary with the stage of leishmaniasis, however uremic condition contributes to reduce the viability of neutrophils in late-stage dogs. Changes of neutrophil oxidative metabolism occur concomitant with oxidative stress and increased neutrophil apoptosis in both leishmaniasis and in uremia alone
Keywords: Stress oxidativo; Neutrofilos; Superoxido; Leishmaniose visceral; Antioxidantes; Uremia; Leishmaniasis